Pregunta
upstudy study bank question image url

Question 1 1.1. Prove that the sum of \( n \) terms of an arithmetic sequence of \( n \) terms is given by the formula: \( S_{n}=\frac{n}{2}[2 a+(n-1) d] \) 1.2. Consider the series: \( 5+8+11+14+17+\ldots+302 \) 1.2.1. Determine the formula for the \( n^{t h} \) term of the series. 1.2.2. How may terms are there in the series? 1.2.3. Express the series in sigma notation. 1.2.4. Determine the sum of the terms in the series. 1.3. Determine the value of \( n \) if 1.4. Expand and evaluate: \( \sum_{k=1}^{n}(3 k-15)=285 \) (2) (2) (2) (2)

Ask by Reid Sanders. in South Africa
Feb 25,2025

Solución de inteligencia artificial de Upstudy

Respuesta verificada por el tutor

Responder

1.1: The sum of \( n \) terms of an arithmetic sequence is \( S_n = \frac{n}{2} [2a + (n-1)d] \). 1.2.1: The \( n^{th} \) term is \( a_n = 3n + 2 \). 1.2.2: There are 100 terms in the series. 1.2.3: The series in sigma notation is \( \sum_{n=1}^{100} (3n + 2) \). 1.2.4: The sum of the series is 15,350. 1.3: Cannot determine \( n \) as the question is incomplete. 1.4: The value of \( n \) is 19.

Solución

Let's solve the problem step by step. ### 1.1 Prove the formula for the sum of \( n \) terms of an arithmetic sequence An arithmetic sequence is defined by its first term \( a \) and a common difference \( d \). The \( n \)-th term of the sequence can be expressed as: \[ a_n = a + (n-1)d \] The sum of the first \( n \) terms \( S_n \) can be calculated as follows: \[ S_n = a + (a + d) + (a + 2d) + \ldots + (a + (n-1)d) \] This can be rewritten as: \[ S_n = na + d(0 + 1 + 2 + \ldots + (n-1)) \] The sum of the first \( n-1 \) integers is given by the formula: \[ \sum_{k=0}^{n-1} k = \frac{(n-1)n}{2} \] Substituting this into the equation for \( S_n \): \[ S_n = na + d \cdot \frac{(n-1)n}{2} \] Factoring out \( n \): \[ S_n = \frac{n}{2} \left( 2a + (n-1)d \right) \] Thus, we have proven that: \[ S_n = \frac{n}{2} [2a + (n-1)d] \] ### 1.2 Consider the series: \( 5 + 8 + 11 + 14 + 17 + \ldots + 302 \) #### 1.2.1 Determine the formula for the \( n^{th} \) term of the series The first term \( a = 5 \) and the common difference \( d = 3 \). The \( n^{th} \) term can be expressed as: \[ a_n = a + (n-1)d = 5 + (n-1) \cdot 3 = 3n + 2 \] #### 1.2.2 How many terms are there in the series? To find the number of terms, we set the \( n^{th} \) term equal to 302: \[ 3n + 2 = 302 \] Solving for \( n \): \[ 3n = 300 \\ n = 100 \] #### 1.2.3 Express the series in sigma notation The series can be expressed in sigma notation as: \[ \sum_{n=1}^{100} (3n + 2) \] #### 1.2.4 Determine the sum of the terms in the series Using the sum formula derived in 1.1, we can calculate \( S_{100} \): \[ S_{100} = \frac{100}{2} [2 \cdot 5 + (100 - 1) \cdot 3] \] Calculating the terms inside the brackets: \[ S_{100} = 50 [10 + 297] = 50 \cdot 307 = 15350 \] ### 1.3 Determine the value of \( n \) if It seems that part 1.3 is incomplete. Please provide the equation or condition to determine \( n \). ### 1.4 Expand and evaluate: \( \sum_{k=1}^{n}(3k-15)=285 \) First, we can expand the sum: \[ \sum_{k=1}^{n} (3k - 15) = 3\sum_{k=1}^{n} k - \sum_{k=1}^{n} 15 \] Using the formula for the sum of the first \( n \) integers: \[ \sum_{k=1}^{n} k = \frac{n(n+1)}{2} \] Thus, we have: \[ \sum_{k=1}^{n} (3k - 15) = 3 \cdot \frac{n(n+1)}{2} - 15n \] Setting this equal to 285: \[ 3 \cdot \frac{n(n+1)}{2} - 15n = 285 \] Multiplying through by 2 to eliminate the fraction: \[ 3n(n+1) - 30n = 570 \] Rearranging gives: \[ 3n^2 - 27n - 570 = 0 \] Dividing through by 3: \[ n^2 - 9n - 190 = 0 \] Now, we can solve this quadratic equation using the quadratic formula: \[ n = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \] Where \( a = 1, b = -9, c = -190 \): Calculating the discriminant: \[ b^2 - 4ac = (-9)^2 - 4 \cdot 1 \cdot (-190) = 81 + 760 = 841 \] Now substituting back into the quadratic formula: \[ n = \frac{9 \pm \sqrt{841}}{2} = \frac{9 \pm 29}{2} \] Calculating the two possible values for \( n \): 1. \( n = \frac{38}{2} = 19 \) 2. \( n = \frac{-20}{2} = -10 \) (not valid since \( n \) must be positive) Thus, the value of \( n \) is: \[ n = 19 \] ### Summary of Answers 1.1: Proven formula for \( S_n \). 1.2.1: \( a_n = 3n + 2 \). 1.2.2: \( n = 100 \). 1.2.3: \( \sum_{n=1}^{100} (3n + 2) \). 1.2.4: \( S_{100} = 15350 \). 1.3: Incomplete. 1.4: \( n = 19 \).

Respondido por UpStudy AI y revisado por un tutor profesional

error msg
Explicar
Simplifique esta solución

The Deep Dive

The formula for the sum of an arithmetic sequence arises from the addition of the first and last terms repeatedly. If you line up the series in reverse and add it to the original, you’ll see that every pair sums to the same value, simplifying to the neat formula involving \( n \), \( a \), and \( d \). It's like a fun mathematical dance where every term finds its perfect partner! When working with arithmetic series like \( 5 + 8 + 11 + 14 + 17 + \ldots + 302 \), remember that the difference between consecutive terms, known as the common difference \( d \), plays a critical role. For this series, \( d = 3 \). To find the total number of terms, use \( n = \frac{(last\ term - first\ term)}{d} + 1 \), which lets you unlock the full count of this beautifully structured sequence!

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad